Felix saeculum Cracoviae – Krakow’s happy age: legend and reality - Łatak, Kazimierz (Saeculum Christianum. Pismo Historyczne, 2024)
This article is a reflection on the phenomenon referred to in Polish historiography as felix saeculum Cracoviae, i.e., Krakow’s happy age. The concept first appeared in the mid-16th century, in a hagiography of blessed Michał Giedroyć (+1489) written by Jan of Trzciana, a professor at the University of Krakow. It was directly associated with a group of six saints/clerics who lived and worked in 15th century Krakow metropolitan area: Jan Kanty, Izajasz Boner, Szymon of Lipnica, Stanisław Kazimierczyk, Michał Giedroyć and Świętosław Milczący. In the early 17th century, the notion laid the foundation for a multi-layer hagiographic construct, which with time began to be used also in reference to the city’s 15th century history, presented as a remarkable period of thriving religious life and a “great era in its spiritual history”. However, an in-depth study of the phenomenon leaves no doubt that the ‘happy age’ is only a beautiful legend far removed from historical reality.